Prevalence and determinants of acanthosis nigricans among adolescents: a school based cross sectional study in Southern Kerala - George, Babu; A. R., Juby Raj; M. L., Leena; Bhaskaran, Deepa; I., Lalikumari; Mahendran, Preema; T., Neethu (International Journal of Research in Dermatology, 2024)
Background: Acanthosis nigricans (AN) is a dermatologic condition that may be associated with various underlying medical conditions and is increasingly seen in obese children and adolescents. Assessing AN in adolescents is crucial as it can serve as an early indicator of underlying insulin resistance and metabolic disorders. Methods: This cross sectional study was conducted among class eleven higher secondary students in public and aided sector in Thiruvananthapuram district of Kerala. A total of 1832 students were recruited using multistage cluster sampling procedure. The participants were examined and neck grading for acanthosis was recorded. Anthropometric readings along with blood pressure, perceived stress levels, family history of diseases as well as life style habits were also evaluated. The female participants were examined for symptoms of anovulation and hyperandrogenism. Results: A total of 1832 students participated in the study of which 66% were girls and 34% were boys. About 26% were found to have AN. Prevalence of Acanthosis was higher in girls (30.3%) compared to boys (18%). Hypertension (OR: 2.83, 95% CI: 2.25-3.55), overweight or obesity (OR: 10.67, 95% CI: 8.26-13.78) and high levels of perceived stress (OR: 1.55, 95% CI: 1.05-2.30) were found to be significantly associated with acanthosis. Conclusions: The findings suggest that AN neck grading can serve as a useful tool for non-communicable disease screening in schools, enabling the identification of students who may require further evaluation and intervention.